Integrated physiological and transcriptomic analyses reveal the mechanism of reduction in wheat fertile floret number under spring low-temperature stress - Ying Weng; Zhiwei Tang; Weixiang Huang; Rui Wang; Feifei Wang; Hongmei Cai; Hao Wang; Zehao Liu; Baoqiang Zheng; Jincai Li; Xiang Chen (Crop Journal)
With the intensification of climate change, spring low-temperature stress (SLTS) leads to floret degeneration and a decrease in grain number. This study investigated the physiological mechanisms underlying SLTS-induced floret degeneration using two wheat varieties with contrasting cold sensitivity. SLTS caused yellowing and shrinkage of floret primordia, increasing floret degeneration and fertile floret abortion, ultimately reducing grains per spike by 12.2%–26.1%. SLTS disrupted nutrient supply, impairing dry matter accumulation in young spikes. At 0–15 d after low-temperature stress (DALTS), SLTS caused a brief increase in the sugar content of young spikes (0–3 DALTS), followed by a rapid decrease (6–15 DALTS), while the total nitrogen content keeps decreasing. SLTS altered key enzyme activities, enhancing sucrose synthase and sucrose phosphate synthase but suppressing nitrate reductase and glutamine synthetase. Transcriptomic analysis revealed that SLTS perturbed starch and sucrose metabolism, carbon and nitrogen metabolism, and amino sugar pathways, altering soluble sugars, sucrose, fructose, and protein levels. SLTS disrupted carbon–nitrogen metabolic homeostasis, thereby reducing the number of fertile florets and ultimately leading to a decrease in grain number per spike. These findings enhance understanding of SLTS impacts on wheat floret development and provide insights for improving low-temperature tolerance and yield stability in wheat.